Quantifying Insect Cell Nutrition for Use in Cellular Agriculture - Soule-Albridge, Erin. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Biomedical Engineering.; Advisor: David Kaplan.; Committee: Barry Trimmer, and Ying Chen.; Keywords: Biomedical engineering, and Nutrition.